Persistent müllerian duct syndrome in canine male of breeds Schnauzer: Case reports - Quintana Avila, Víctor Manuel; Galeano Pinilla, Yeferson Andrey; Pulido-Medellín, Martín Orlando (Spei Domus, 2023)
Case report study where the syndrome of persistence of the Mullerian ducts in male canines of the Schnauzer breed is analyzed, characterizing the symptomatology associated with the presence of pyometra in cases of pseudohermaphroditism, this is part of a process of sexual differentiation that is It begins in the uterus and continues in development until reaching maturity, dividing into three phases: chromosomal, gonadal and phenotypic sex, an alteration in sexual development is the syndrome of persistent Mullerian ducts that is present in cases of apparent hermaphroditism male, which is hereditary, autosomal, recessive in XY individuals, in which the presence of the uterus and other structures of the female reproductive tract is observed in a male animal, derived from an interference in the response to the anti-Müllerin hormone at the receptor, which has been reported in dogs of the Miniature Schnauzer breed, from this perspective in this article we report So three clinical cases observed in a veterinarian in Bucaramanga, the symptoms reported indicate episodes of decay, fever, diarrhea, abdominal palpation pain and tenesmus, alterations in blood chemistry, in the clinical examination pyometra was observed, and purulent dripping discharge from of the urethra, gynecomastia and cryptorchism, recurrent appearance in cases of canine pseudohermaphroditism.
Keywords: male pseudohermaphroditism; persistence syndrome; Schnauzer